2007
DOI: 10.1007/s00415-006-0335-4
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of physiotherapist prescribed community based exercise in inflammatory peripheral neuropathy

Abstract: There is insufficient evidence to support the use of exercise in the management of chronic disablement in people with inflammatory peripheral neuropathy. Therefore, our study aimed to determine the feasibility and effectiveness of a physiotherapist prescribed community based exercise programme for reducing chronic disablement in patients with stable motor neuropathy. We assessed the effects of a 12 week unsupervised, community based strengthening, aerobic and functional exercise programme on activity limitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
37
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 41 publications
5
37
0
Order By: Relevance
“…Insert Table 2 here During the intervention a varied response was seen regarding walking speeds and be an effect of the exercise intervention, however it could also be explained by the 21 masking of the additional gains of the faster walking participants as they were near In line with Graham et al [14] our participants also reported to be less fatigued, 5 although this was not significant. A study encompassing more participants and 6 perhaps a longer or more intense intervention could show a significant result.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…Insert Table 2 here During the intervention a varied response was seen regarding walking speeds and be an effect of the exercise intervention, however it could also be explained by the 21 masking of the additional gains of the faster walking participants as they were near In line with Graham et al [14] our participants also reported to be less fatigued, 5 although this was not significant. A study encompassing more participants and 6 perhaps a longer or more intense intervention could show a significant result.…”
supporting
confidence: 54%
“…A study encompassing more participants and 6 perhaps a longer or more intense intervention could show a significant result. The 7 reduced fatigue levels in this study could be caused by increased strength levels due 8 to the intervention, but could also be explained by the possibility that participants 9 were less depressed due to improved Quality of Life, became less depressed, 10 became less anxious of the assessments over time or by the day to day variability 11 seen in this disease [14]. Although the latter is possible this study used an average 12 of three assessments and assessed the participants at set time points to limit this 13 effect.…”
mentioning
confidence: 95%
“…To prevent deterioration and facilitate physical activity, physical therapy may be needed for patients with residual symptoms. Although evidence is scarce, exercise seems to improve physical functioning [29,30].…”
Section: Discussionmentioning
confidence: 97%
“…Recognition of fatigue as a late and disabling symptom after apparent recovery from GBS is important, as physical and behavioral therapy programs may help coping better with the complaints and improve quality of life [21,22].…”
Section: Discussionmentioning
confidence: 99%